Analisis Studi Kelayakan Bisnis Terhadap Usaha Pangsit Chili Oil - Andryanti Natanegara, Aura Syahida; Dwi Nurmavita, Diah Ayu; Rasmana, Idan; Ilmi, Haura Nurul; Perwito, Perwito (UNIVERSITAS SERAMBI MEKKAH, 2025)
The culinary industry in Indonesia continues to grow rapidly, especially in the innovative fast food category. One product that is increasingly in demand is chili oil chicken dumplings, which combine chicken dumplings with a signature chili oil sauce. This product offers a spicy, savory, and delicious taste with various levels of spiciness that can be adjusted according to consumer tastes. With the increasing demand for fast food, the chili oil chicken dumpling business has a wide and promising market opportunity. However, to ensure the sustainability of this business, a business feasibility study is needed that covers various important aspects, such as marketing, human resources, operations, and finance. This research uses a qualitative method with an observation and case study approach to analyze the opportunities and challenges in the chili oil chicken dumpling business. The results show that fast food remains the top choice of the public, especially young people and housewives, who prioritize convenience as well as nutritional quality. Therefore, entrepreneurs who want to enter this business must consider food safety factors, information transparency, and environmental sustainability to build consumer trust and market competitiveness.